The ALPINE-ALMA [C ii] Survey: kinematic diversity and rotation in massive star-forming galaxies at z 4.4–5.9. Issue 3 (9th August 2021) - Jones, G C; Vergani, D; Romano, M; Ginolfi, M; Fudamoto, Y; Béthermin, M; Fujimoto, S; Lemaux, B C; Morselli, L; Capak, P; Cassata, P; Faisst, A; et al.
ABSTRACT: While the kinematics of galaxies up to z ∼ 3 have been characterized in detail, only a handful of galaxies at high redshift ( z > 4) have been examined in such a way. The Atacama Large Millimeter/submillimeter Array (ALMA) Large Program to INvestigate [C ii ] at Early times (ALPINE) survey observed a statistically significant sample of 118 star-forming main-sequence galaxies at z = 4.4–5.9 in [C ii ]158 μ m emission, increasing the number of such observations by nearly 10×. A preliminary qualitative classification of these sources revealed a diversity of kinematic types (i.e. rotators, mergers, and dispersion-dominated systems). In this work, we supplement the initial classification by applying quantitative analyses to the ALPINE data: a tilted ring model (TRM) fitting code ( 3D barolo ), a morphological classification (Gini-M20 ), and a set of disc identification criteria. Of the 75 [C ii ]-detected ALPINE galaxies, 29 are detected at sufficient significance and spatial resolution to allow for TRM fitting and the derivation of morphological and kinematic parameters. These 29 sources constitute a high-mass subset of the ALPINE sample (M_*10^9.5 M_ ). We robustly classify 14 of these sources (six rotators, five mergers, and three dispersion-dominated systems); the remaining sources showing complex behaviour. By exploring the G-M20 of z > 4 rest-frame far-infrared and [C ii ] data for the first time, we find that our 1 arcsec ∼ 6 kpc resolution data alone are insufficient to separate galaxy types. We compare the rotation curves and dynamical mass profiles of the six ALPINE rotators to the two previously detected z ∼ 4–6 unlensed main-sequence rotators, finding high rotational velocities (∼50–250 km s −1 ) and a diversity of rotation curve shapes.